2018
DOI: 10.1016/j.neurol.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain molecular imaging in pharmacoresistant focal epilepsy: Current practice and perspectives

Abstract: This review aims to synthesize all the available data on brain molecular imaging, such as single-photon emission computed tomography (SPECT) and interictal fluorodeoxyglucose positron emission tomography (FDG-PET), in focal epilepsies. SPECT imaging is able to measure regional cerebral blood flow and its major innovation remains its ictal imaging value. On the other hand, FDG-PET, which has higher spatial resolution and lower background activity than SPECT, enables glycolytic metabolism to be identified in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…Its predictive value for epileptogenic zone and surgical outcome has been reported, especially for temporal lobe epilepsy . Studies of PET data from epilepsy patients have shown correlation of hypometabolism and epileptogenicity, or the topography of abnormal metabolism, which can imply a dysfunctional neural network . However, how PET scans often show hypometabolism beyond the presumed epileptogenic zone 8 and how they are relatively less sensitive in analyzing extratemporal lobe epilepsies can be confounding for patients with intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Its predictive value for epileptogenic zone and surgical outcome has been reported, especially for temporal lobe epilepsy . Studies of PET data from epilepsy patients have shown correlation of hypometabolism and epileptogenicity, or the topography of abnormal metabolism, which can imply a dysfunctional neural network . However, how PET scans often show hypometabolism beyond the presumed epileptogenic zone 8 and how they are relatively less sensitive in analyzing extratemporal lobe epilepsies can be confounding for patients with intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews on PET and SPECT in presurgical evaluation were published during this period [ 31 ▪▪ , 56 ▪▪ – 59 ▪▪ , 60 ▪ ].…”
Section: Reviewsmentioning
confidence: 99%
“…Today, brain perfusion SPECT is considered to be highly indicated (i) to image and localize the foci of epilepsy after injection of a perfusion tracer in the ictal state, whereas such ictal imaging is impossible with FDG PET [ 3 ]; (ii) to evaluate chronic cerebral ischemia with acetazolamide challenge, in order to detect areas of critically reduced perfusion [ 35 ]; and (iii) as an alternative to FDG PET for assessment of neurodegenerative disorders, particularly in diabetic patients for whom brain FDG-PET should be acquired in normal glycemia conditions [ 36 , 37 ]. The new CZT cameras have also potential for new indications that may not be achievable with brain PET imaging.…”
Section: Discussionmentioning
confidence: 99%